Promosi Promosi Layanan Anak Dinas Arsip dan Perpustakaan Daerah Kabupaten Buleleng, Bali: Layanan Anak - Irinia Azizah (ACARYA PUSTAKA, 2025)
Abstract The Regional Archives and Library Department (DAPD) of Buleleng Regency seeks to expand the reach of children's services to remote schools in the Buleleng region, this is the basis for researchers to find out the promotions carried out and the challenges faced by DAPD Buleleng Regency. This research aims to: (1) find out the reasons why Buleleng District DAPD promotes children's services; (2) find out the children's services promotion strategy that is applied; and (3) find out the challenges faced by DAPD in conducting promotions. The research method used is descriptive qualitative to make a picture, description systematically, factually, and accurately about the facts, phenomena investigated, with the approach of observation, interviews and document studies. The research informants consisted of four DAPD parties, two additional informants. The results showed that: (1) the promotion of children's services aims to improve children's literacy in Buleleng Regency and foster their love for libraries; (2) the promotional strategies carried out include conventional methods such as direct visits to schools, and online methods through social media such as websites, YouTube, and Instagram; and (3) challenges include the geographical location of schools that are difficult to reach, limited human resources, and lack of supporting facilities and infrastructure for promotion. This research systematically examines the efforts and constraints of Buleleng District DAPD in promoting library services to improve literacy among children, especially in remote areas. Keywords: promotion, children's services, public library, literacy, mobile librar